Determining the Clinical Utility of 16S rRNA Sequencing in the Management of Culture-Negative Pediatric Infections - Peter Paul C. Lim; Lisa M. Stempak; Sindhoosha Malay; LeAnne N. Moore; Sree Sarah S. Cherian; Ankita P. Desai (MDPI AG, 2022)
The use of 16S rRNA sequencing in culture-negative infections has improved identification of bacterial pathogens in select scenarios, but its clinical impact requires further elucidation, especially in the pediatric population. This retrospective study aims to determine the clinical utility of 16S rRNA sequencing on the clinical management of pediatric culture-negative infections in our institution. Significant clinical utility was identified in 30 (40.5%) of 74 clinical samples (p < 0.0001). Of all specimens, pulmonary samples yielded the most clinical utility (n = 9, 30%), followed equally by joint fluid (n = 6, 20%) and bone (n = 6, 20%), with no difference between fluid and fresh tissue specimens (p = 0.346). Although the difference was not statistically significant (p = 0.4111), the overall use of broad-spectrum coverage was decreased. The median number of antibiotics was decreased from two to one (p < 0.0001) based on 16S rRNA sequencing results. The results suggest that 16S rRNA sequencing has a significant impact on decreasing the number of antibiotics used in the treatment of pediatric culture-negative infections. 16S rRNA sequencing performed on pulmonary specimens has the highest likelihood of identifying a pathogen compared to other specimen types. Additional cost-benefit analysis needs to be completed to further determine clinical benefit.